How to Implement Game-Based Learning in a Smart Classroom? A Model Based on a Systematic Literature Review and Delphi Method - Pan, Liuxia; Tlili, Ahmed; Li, Jiaping; Jiang, Feng; Shi, Gaojun; Yu, Huiju; Yang, Junfeng (Frontiers in Psychology, 2021)
Game-based learning (GBL) can allow learners to acquire and construct knowledge in a fun and focused learning atmosphere. A systematic literature review of 42 papers from 2010 to 2020 in this study showed that the current difficulties in implementing GBL in the classroom could be classified into the following categories: infrastructure, resources, theoretical guidance, teacher’s capabilities and acceptance of GBL. In order to solve the above problems, the study constructs a technology enhanced GBL model, from the four parts of learning objective, learning process, learning evaluation, and smart classroom. In addition, this study adopted the Delphi method, inviting a total of 29 scholars, experts, teachers and school managers, in order to explore how to implement GBL in a smart classroom. Finally, the technology enhanced GBL model was validated and the utilization approaches were provided at the conclusion part.